Rôle et place de la chèvre dans les ménages du Sahel burkinabé - Gnanda, BI. (Tropicultura, 2016)
Role and Position of the Goat in Households of the Burkinabian Sahel. A formal household survey was carried out in Burkina Faso with 150 Sahelian farms in order to appreciate the role and the position of goat breeding in the life and the functioning of these family units. The results of the investigation show that the Burkinabe Sahelian stockbreeders first start usually by raising a goat, because of its high prolificacy, but with the view to acquire more or less rapidly other species of ruminants, in particular cattle. Although the generation of income of goat rearing remains low compared to other ruminants (bovine, ovine); their non-monetary role in poverty alleviation is highlighted. That is shown through the large proportion of the population (91% of the target-group) implied in goat breeding, the first position of goats in the non-commercial (social) transaction, and their position in terms of risk prevention against the climatic hazards for livestock farmers. Despite its critical role, the goat remains the least favored ruminant species in regarding health protection and food supplementation.